The moral in Paulo Freire's educational work: What moral education can learn from Paulo Freire. Issue 4 (2nd October 2017) - Veugelers, Wiel
Abstract: The Brazilian pedagogue Paulo Freire had a great influence on theory and practice of education across the world. Freire presented his theory and work as educational and political, not as moral. In this article, the legacy of Paulo Freire will be analysed from a moral education perspective. Nine pedagogical principles will be presented and the changes he contributed in different academic disciplines will be analysed. We conclude that in particular, his focus on social justice, empowerment and transformation can make moral education more linked to society, and more part of a process of humanisation.